The impact of the transgenic revolution on aquaculture and biodiversity. A review - Pérez, Julio; Mayz, Juliana; Rylander, Kent; Nirchio, Mauro (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
We discuss the aims and techniques of transgenics and examine some consequences of incorporating genetic modified organisms (GMs) into the aquaculture industry, as well as introducing them into native habitats. The detrimental effects of introducing transgenic organisms into native habitats include the extinction of indigenous species, the dispersal of transgenes to non-engineered organisms, and in some areas a negative impact on biodiversity. In view of possible adverse effects of genetically modified finfish, shellfish and crustaceans. Programs of monitoring that must carried out before the release of GMs into aquaculture installations, are strongly recommended. Transgenic research with altered temperatures or salinity tolerance should be avoided. Such GMs could enter and persist in communities that are not adapted to their presence. Furthermore it is clearly unwise to cultivate transgenic organims in environments where populations of the same or closely related species live.